Mental Health Outcomes and Their Correlates in The Post-COVID-19 Era Among University Students and Staff in Indonesia - Noor Alis Setiyadi; Irfanul Chakim; Ekha Rifki Fauzi; Okti Sri Purwanti; Sari Andajani; Lianawati; Lord Joseas Conwi; Kittipong Sornlorm (National Journal of Community Medicine)
Background: The COVID-19 pandemic has profoundly affected global health, particularly mental health in academic communities. While its impact on mental health is well-documented, studies on the post-pandemic "new normal" remain scarce. This study examines the prevalence and factors linked to anxiety, depression, and QoL among Indonesian university students, lecturers, and staff post-pandemic.